Hafidz Qur'an and Its Influence toward High School Students Learning Achievement in Indonesia - Muh. Arif; Iswan Nggolitu (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2019)
This article elaborates on the achievements of the memorization of the Qur'an in the achievement of students’ learning in Gorontalo. These studies focus on the ability of the haafiz (memorizer) Qur'an in Islamic High School Student of Insan Cendekia Gorontalo is not less than of 5 juz as set forth in the vision and the tahfidz Qur'an syllabus started from semester 1 to 5 with should memorize juz. Thus, division is made up of 30 juz 1 to with juz 4 so that as a whole was 5 juz. The ability of the haafiz Quran obtained the rate of speed and the number of the surah memorized by any learners differ between each other so that the teacher provide different methods in activity recite on the activity or activities tahfiz tasmi' performed at dawn by a fellow colleague. The results showed that the impact of learning achievements by the Qur'an haafiz learners on the subjects of Hadith and Qur'an natural science (IPA) in the Islamic High School Student of Insan Cendekia Gorontalo was shown by the results of the assessment of learning achievements of students on subjects.